Hanging around, pottering about, chilling out: lessons on silence and well-being from Summerhill school - Lees, Helen E. (Revista Hipótese, 2017)
This paper highlights moments of the doing of “nothing much” as beneficial and educative as pedagogy for all schools. It uses Summerhill School, Suffolk, UK as an example of a school where chosen silence of a cumulative, positive, “strong” kind is valued – in the form of children choosing to hang about, potter about, chill out - and which as a school has this facilitation of the doing of nothing much to teach to other school settings.